PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN SERTA IMPLIKASINYA TERHADAP LOYALITAS PELANGGAN KOPER RIMOWA PADA STORE MAL PLAZA INDONESIA DI JAKARTA (PT METROX GLOBAL) - Ismoerida Ismoerida; Lisnawati Sufriani Tobing (Jurnal Manajemen FE-UB, 2018)
The growth of retail business, especially modern retail business is growing rapidly in Indonesia especially Jakarta. This study aims to analyze deeper the Influence of Service Quality (X1) and Price (X2) on Consumer Decision (Y) and its implications to Customer Loyalty (Z). Sempel taking technique using accidental sampling is based on chance which means consumers who buy luggage products Rimowa on Store Mal Plaza Indonesia, with the number of samples obtained as much as 98 respondents. Data analysis technique used in this research is by PathAnalysis method and using analysis tool that is SPSS 22. The test results indicate that the variable of Service Quality has positive and significant influence directly to the satisfaction of Consumer. Price has positive and significant effect directly to Customer Satisfaction. Quality of service has a positive but not directly significant effect on Customer Loyalty. Price has positive and significant effect directly to Customer Loyalty. Consumer Satisfaction has positive and significant effect directly to Customer Loyalty. Service Quality positively and indirectly affects Customer Loyalty through Customer Satisfaction. And Price affects positively and indirectly significant to Customer Loyalty through Customer Satisfaction. Keywords: Service Quality, Price, Customer Satisfaction and Customer Loyalty of Rimowa at Mall Plaza Indonesiadi Jakarta (PT Metrox Global).